The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1136/jmedgenet-2013-102240
|View full text |Cite
|
Sign up to set email alerts
|

ADAP2in heart development: a candidate gene for the occurrence of cardiovascular malformations in NF1 microdeletion syndrome

Abstract: Overall, our findings indicate that ADAP2 has a role in heart development, and might be a reliable candidate gene for the occurrence of cardiovascular malformations in patients with NF1 microdeletion and, more generally, for the occurrence of a subset of congenital heart defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
1
24
0
4
Order By: Relevance
“…The heat maps show how genes are clustered across the control and hace1-morpholino knockdown samples (vertical) and along the spectrum and pattern of gene fold changes (horizontal). Similar looping defects were seen in morphants for adap2 (Venturin et al, 2014), slc8a4a (ncx4a) (Shu et al, 2007), and foxj1b . B: Genes associated with "heart development" Gene Ontology term.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The heat maps show how genes are clustered across the control and hace1-morpholino knockdown samples (vertical) and along the spectrum and pattern of gene fold changes (horizontal). Similar looping defects were seen in morphants for adap2 (Venturin et al, 2014), slc8a4a (ncx4a) (Shu et al, 2007), and foxj1b . B: Genes associated with "heart development" Gene Ontology term.…”
Section: Discussionsupporting
confidence: 61%
“…The bone morphogenic protein receptors Bmpr2a and Bmpr2b, for example, act upstream of the critical LR regulator Nodal; knockdown of either of these genes causes significant looping defects in affected embryos (Monteiro et al, 2008). Similar looping defects were seen in morphants for adap2 (Venturin et al, 2014), slc8a4a (ncx4a) (Shu et al, 2007), and foxj1b . Interestingly, lmo7 morphants display a similar tubular heart phenotype to our hace1 morphants (Ott et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Disturbances of the cytoskeletal organisation in myocytes during embryonal development may be responsible for the cardiovascular malformations observed in patients with NF1 microdeletions. This postulate was reinforced by the findings of Venturin et al (2014) who showed that in zebrafish, ADAP2 is required for normal cardiac morphogenesis.…”
Section: Co-deleted Genes With the Potential To Influence The Clinicamentioning
confidence: 82%
“…This conclusion is drawn from the observation that ADAP2 is highly expressed during early stages of heart development in both mouse and human (Venturin et al 2005, 2014). In zebrafish, ADAP2 loss of function leads to circulatory deficiencies and heart shape defects or defective valvulogenesis (Venturin et al 2014). The ADAP 2-encoded protein acts as a GTPase-activating protein (GAP) of the ADP-ribosylation factor 6 (ARF6), a small GTPase involved in actin cytoskeleton remodelling.…”
Section: Co-deleted Genes With the Potential To Influence The Clinicamentioning
confidence: 99%
“…While these data potentially exclude other members from having any role in regulating the interferon response, it should be kept in mind that the RNAi screening study did not validate the silencing efficiency and on-target specificity of the siRNAs used against other members of the ArfGAP family. Other known functions of ADAP2 include regulation of heart development and stabilization of microtubules (66,70,71). Collectively, all the evidence provides an increased appreciation of the roles of ArfGAP family proteins in host-pathogen interactions.…”
Section: Discussionmentioning
confidence: 91%